The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1136/bmj.m3173
|View full text |Cite
|
Sign up to set email alerts
|

Association between nutritional profiles of foods underlying Nutri-Score front-of-pack labels and mortality: EPIC cohort study in 10 European countries

Abstract: Objective To determine if the Food Standards Agency nutrient profiling system (FSAm-NPS), which grades the nutritional quality of food products and is used to derive the Nutri-Score front-of-packet label to guide consumers towards healthier food choices, is associated with mortality. Design Population based cohort study. Setting European Prospective Investigation into Cancer and Nutrition (EPIC) cohort from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 61 publications
2
72
0
Order By: Relevance
“…However, the main determinant of the ora was not established, and the study involved a small sample size. Deschasaux [44] studied the gut ora of more than 2,000 individuals of different ethnicities in the same city and showed that ethnicity contributes signi cantly to individual differences in the gut microbiome, independent of metabolic health. Accordingly, studies of human ora should consider ethnicity as a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main determinant of the ora was not established, and the study involved a small sample size. Deschasaux [44] studied the gut ora of more than 2,000 individuals of different ethnicities in the same city and showed that ethnicity contributes signi cantly to individual differences in the gut microbiome, independent of metabolic health. Accordingly, studies of human ora should consider ethnicity as a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main determinant of the ora was not established, and the study involved a small sample size. Deschasaux [44] studied the gut ora of more than 2,000 individuals of different ethnicities in the same city and showed that ethnicity contributes signi cantly to individual differences in the gut microbiome, independent of metabolic health. Accordingly, studies of human ora should consider ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…In 10 European countries, mostly high income, consuming higher-scoring foods (i.e. lower quality diets) was associated with a higher mortality for all causes and for cancer and diseases of the circulatory, respiratory, and digestive systems ( 77 ). However, linking NP models with health outcomes is region or population specific and depends on the leading causes of a health burden in a given society.…”
Section: Ghana—a Case Studymentioning
confidence: 99%